Relation between Level of Some Immunological Markers and Liver Functions with Respiratory Bacterial Infection in Sheep - Mustafa Ghazi Saeed; Bashar SadeqNoomi; Entedhar Rifaat Sarhat (Institute of Medico-legal Publications Pvt Ltd, 2021)
Sheep pneumonia remains an important cause of morbidity and mortality worldwide. The aim of the studyreport to determine Interleukine-6,IL-10,and liver function test , and kidney function test of sheep sufferingfrom respiratory disease. Blood samples were collected from the diseased and healthy sheep during fieldstudy, for biochemical analysis. The results of 50 diseased animals were compared with results of 50 healthyanimals.Data of selected biochemical parameters implicated a significant increase in Interleukin-6, alanineaminotransferase and aspartate aminotransferase, and Gamma glutamyltransferase in the diseased groupcompared to the healthy sheep’s. On the other hand, a significant decrease was seen in the levels of IL-10, lactate dehydrogenase and total protein in the diseased group compared to the control. The results ofthis study could conclude that respiratory infections in sheep were associated with significant biochemicaland immunological alterations which upon understanding can provide us with rapid diagnostic tools forpneumonia process in sheep and thus lead to better management and proper treatment.Future research iswarranted to determine the response of individual animals to this disease and to describe the metabolicchanges which occur during the course of respiratory diseases.